Study on the LES of Premixed Gas Flame Dynamics in a Weak Confinement Structure: The Influence of Continuous Obstacle Plates - X. Shao; J. Gao; B. Hao; B. Ai; Y. Han; Y. Wu; B. Guo (Journal of Applied Fluid Mechanics)
The layout of equipment and structures in underground utility tunnels has a significant impact on the safety of spaces. In this paper, experimental and simulation methods are combined to investigate the detonation characteristics of propane(C3H8)-air mixtures. By placing continuous obstacle plate at different positions within a pipeline, we examine the flame behavior, pressure, and flow field during the detonation process. The findings reveal that continuous obstacles create greater disturbances than single obstacles. When continuous obstacles are placed 500 mm and 800 mm from the ignition point, a secondary reignition phenomenon occurs; however, there is little difference in the time it takes for the flame front to reach the pipe’s outlet. Additionally, when continuous obstacles are positioned 200 mm and 800 mm from the ignition point, the detonation reaction weakens, with pressure peak reductions of 8.57% and 3.98% compared to the case with three single obstacles, and the maximum flame area decreases by 6.60% and 2.19%. In contrast, placing obstacles at 500 mm heightens the detonation reaction, resulting in a 2.92% increase in the pressure peak and a 19.87% increase in the maximum flame area compared to the case with three single obstacles.